Mediterranean Diet Supplemented With Coenzyme Q10 Modulates the Postprandial Metabolism of Advanced Glycation End Products in Elderly Men and Women. (21st October 2016) - Lopez-Moreno, Javier; Quintana-Navarro, Gracia M; Delgado-Lista, Javier; Garcia-Rios, Antonio; Alcala-Diaz, Juan F; Gomez-Delgado, Francisco; Camargo, Antonio; Perez-Martinez, Pablo; Tinahones, Francisco J; Striker, Gary E; Perez-Jimenez, Francisco; Villalba, Jose M; et al.
Abstract: Advanced glycation end products (AGEs) and oxidative stress are elevated with aging and dysmetabolic conditions. Because a Mediterranean (Med) diet reduces oxidative stress, serum AGEs levels, and gene expression related to AGEs metabolism in healthy elderly people, we studied whether supplementation with coenzyme Q10 (CoQ) was of further benefit. Twenty participants aged ≥ 65 (10 men and 10 women) were randomly assigned to each of three isocaloric diets for successive periods of 4 weeks in a crossover design: Med diet, Med + CoQ, and a Western high-saturated-fat diet (SFA diet). After a 12-hour fast, volunteers consumed a breakfast with a fat composition similar to the previous diet period. Analyses included dietary AGEs consumed, serum AGEs and AGE receptor-1 (AGER1), receptor for AGEs (RAGE), glyoxalase I (GloxI), and estrogen receptor α (ERα) mRNA levels. Med diet modulated redox-state parameters, reducing AGEs levels and increasing AGER1 and GloxI mRNA levels compared with the SFA diet. This benefit was accentuated by adding CoQ, in particular, in the postprandial state. Because elevated oxidative stress/inflammation and AGEs are associated with clinical disease in aging, the enhanced protection of a Med diet supplemented with CoQ should be assessed in a larger clinical trial in which clinical conditions in aging are measured.